Improved propagation methods to raise the productivity of yam (dioscorea rotundata poir.) (2015)
White Guinea yam (Dioscorea rotundata Poir.) is an important staple to millions of people in West Africa. Obtaining good quality planting material for yam cultivation is a major challenge. Multiplication ratios are low, and seed tubers are prone to contamination with pests and pathogens in the traditional systems of production. Some approaches to producing quality seed of yam are as follows: farmers select small whole tubers from a ware crop harvest; stimulate the production of seed tubers by ‘milking’ ware tubers while the leaves of the plant are still green (double harvest system); cut ware tubers into setts about the same sizes as regular seed tubers; or use the ‘Anambra’ system where smaller setts are cut and used to produce seed tubers. New methods that have been developed to address some of the challenges of quantity and quality of seed tubers are not yet widely applied, so farmers continue to use traditional methods and save seed from a previous harvest to plant the ware crop. This document presents an overview of traditional and modern methods of seed yam production and gives a perspective for the future. Among the modern methods of seed yam production, only the minisett technique, which uses 25–100 g tuber pieces, is currently used at farmer level, although on a limited scale. While tissue and organ culture techniques are the most rapid methods of multiplying disease free propagules, their limitations include high costs, need for skilled personnel and specialized equipment. The aeroponics and temporary immersion bioreactor methods of producing seed yam are relatively new, and still need more research. To build and sustain a viable seed yam production system, a multiplication scheme is required that combines two or more methods including tissue culture for cleaning the seed stock.